WTO Panel Rules Against U.S. Claim that Tariffs on Chinese Goods Are Justified as Necessary to Protect "Public Morals". Issue 1 (January 2021) - Unknown
Abstract : On September 15, 2020, a World Trade Organization (WTO) panel ruled that certain tariffs the United States imposed on Chinese products violated Articles I (most-favored-nation) and II (tariff bindings) of the General Agreement on Tariffs and Trade (GATT). The panel rejected the U.S. attempt to invoke a "public morals" defense pursuant to GATT Article XX, holding that although countries receive substantial deference in defining "public morals, " the United States failed to prove that the tariffs were necessary to achieve its stated public morals objective.